2018
DOI: 10.3390/ijms19113548
|View full text |Cite
|
Sign up to set email alerts
|

Interferons and Dry Eye in Sjögren’s Syndrome

Abstract: Various cytokines, including interferon (IFN)-γ and IL-17, are augmented, and autoreactive T cells and B cells are activated in the immune pathogenesis of Sjögren’s syndrome (SS). In particular, IFNs are involved in both the early stages of innate immunity by high level of type I IFN in glandular tissue and sera and the later stages of disease progression by type I and type II IFN producing T cells and B cells through B cell activating factor in SS. Genetically modified mouse models for some of these molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 68 publications
(99 reference statements)
3
33
0
1
Order By: Relevance
“…IL-33 expression is upregulated in the salivary glands of pSS patients and acts synergistically with IL-12 and IL-23 to stimulate IFN-γ secretion by NK cells, which contributes to pSS pathogenesis (72,73). The overexpression of IL-12 in SS was also shown to participate in the differentiation of helper T (Th)1 cells and IFN-γ production (74,75); and activation of IFN signaling and the recruitment of pDCs to the salivary glands of pSS patients may promote NK cell activation and IFN-γ production, thereby aggravating disease pathogenesis (71,76,77).…”
Section: Nk Cells and Sjögren's Syndromementioning
confidence: 99%
“…IL-33 expression is upregulated in the salivary glands of pSS patients and acts synergistically with IL-12 and IL-23 to stimulate IFN-γ secretion by NK cells, which contributes to pSS pathogenesis (72,73). The overexpression of IL-12 in SS was also shown to participate in the differentiation of helper T (Th)1 cells and IFN-γ production (74,75); and activation of IFN signaling and the recruitment of pDCs to the salivary glands of pSS patients may promote NK cell activation and IFN-γ production, thereby aggravating disease pathogenesis (71,76,77).…”
Section: Nk Cells and Sjögren's Syndromementioning
confidence: 99%
“…Pro-inflammatory cytokines are known to promote lacrimal gland destruction (in a CD25 knockout model of Sjogren’s syndrome), goblet cell loss, keratinization of the conjunctival epithelium, as well as its apoptosis (in a dry eye mouse model), and tear film instability, all potentially aggravating DED [ 60 , 61 ]. Cytokines are also detected in the tear film and conjunctival epithelium obtained from DED patients, inducing inflammation of the ocular surface [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of vast array of clinical presentation and pathological findings it is assumed that IFN expression pattern will vary among individuals and the systemic IFN type I and type II signature will influence the severity of disease. [36][37][38][39] IFN-γ is the key interferon involved in most of the pathways that have been identified in the pathogenic processes of Sjogren's syndrome. 29 It has been suggested that genetic associations of SS include, interferon regulatory factor-5 (IRF-5) and the IFN signalling pathway.…”
Section: Role Of Interferon In Ded Associated With Pssmentioning
confidence: 99%
“…29 It has been suggested that genetic associations of SS include, interferon regulatory factor-5 (IRF-5) and the IFN signalling pathway. [36][37][38]40 IL-1β and IFN-γ play a pivotal role in squamous metaplasia of the ocular surface epithelium in response to chronic inflammation. 36 Th1 cells and NK cells infiltrate at the ocular surface and release IFN-γ during the process of squamous metaplasia and as result of which both the cytokines are seen at the ocular surface in dry eyes.…”
Section: Role Of Interferon In Ded Associated With Pssmentioning
confidence: 99%